Selective inhibition of PI3K/Akt/mTOR signaling pathway regulates autophagy of macrophage and vulnerability of atherosclerotic plaque. - Chungang Zhai; Jing Cheng; Haroon Mujahid; Hefeng Wang; Jing Kong; Yue Yin; Jifu Li; Yun Zhang; Xiaoping Ji; Wenqiang Chen (PLoS ONE, 2014)
Macrophage infiltration contributes to the instability of atherosclerotic plaques. In the present study, we investigated whether selective inhibition of PI3K/Akt/mTOR signaling pathway can enhance the stability of atherosclerotic plaques by activation of macrophage autophagy. In vitro study, selective inhibitors or siRNA of PI3K/Akt/mTOR pathways were used to treat the rabbit's peritoneal primary macrophage cells. Inflammation related cytokines secreted by macrophages were measured. Ultrastructure changes of macrophages were examined by transmission electron microscope. mRNA or protein expression levels of autophagy related gene Beclin 1, protein 1 light chain 3 II dots (LC3-II) or Atg5-Atg12 conjugation were assayed by quantitative RT-PCR or Western blot. In vivo study, vulnerable plaque models were established in 40 New Zealand White rabbits and then drugs or siRNA were given for 8 weeks to inhibit the PI3K/Akt/mTOR signaling pathway. Intravascular ultrasound (IVUS) was performed to observe the plaque imaging. The ultrastructure of the abdominal aortic atherosclerosis lesions were analyzed with histopathology. RT-PCR or Western blot methods were used to measure the expression levels of corresponding autophagy related molecules. We found that macrophage autophagy was induced in the presence of Akt inhibitor, mTOR inhibitor and mTOR-siRNA in vitro study, while PI3K inhibitor had the opposite role. In vivo study, we found that macrophage autophagy increased significantly and the rabbits had lower plaque rupture incidence, lower plaque burden and decreased vulnerability index in the inhibitors or siRNA treated groups. We made a conclusion that selective inhibition of the Akt/mTOR signal pathway can reduce macrophages and stabilize the vulnerable atherosclerotic plaques by promoting macrophage autophagy.